2022
DOI: 10.1155/2022/1215097
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-Rich Extract of Thespesia garckeana F. Hoffm. (Snot Apple) Contains Potential Drug-Like Candidates and Modulates Glycemic and Oxidoinflammatory Aberrations in Experimental Animals

Abstract: The present study evaluated the polyphenolic contents and hypoglycemic, antioxidant, and anti-inflammatory effects of the diethyl ether fraction of Thespesia garckeana using various in vitro and in vivo models. Total phenol and flavonoid contents of the extract were 613.65 ± 2.38 and 152.83 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
3
2
0
Order By: Relevance
“…The current data on RBG, IPGTT, and AUC showed that luteolin could generate a slightly hypoglycemic effect on DR mice, with weight loss reversed in STZ-induced diabetic mice in later phases ( Figures 7A–D , p > 0.05 vs. model). The finding was in accordance with relevant research reports ( Alozieuwa et al, 2022 ; Ali et al, 2023 ). Nonetheless, as shown in Figures 7A–D , HF with different concentrations failed to reduce RBG ( p all >0.05 vs. model).…”
Section: Resultssupporting
confidence: 93%
“…The current data on RBG, IPGTT, and AUC showed that luteolin could generate a slightly hypoglycemic effect on DR mice, with weight loss reversed in STZ-induced diabetic mice in later phases ( Figures 7A–D , p > 0.05 vs. model). The finding was in accordance with relevant research reports ( Alozieuwa et al, 2022 ; Ali et al, 2023 ). Nonetheless, as shown in Figures 7A–D , HF with different concentrations failed to reduce RBG ( p all >0.05 vs. model).…”
Section: Resultssupporting
confidence: 93%
“…However, the stabilizing effect of this supplementation may take more than four (4) weeks before the manifestation of the stabilizing effect can be observed. This work agrees with the works of Alozieuwa et al (2022), whose study shows that the experimental evidence offered substantiates the therapeutic effectiveness of the diethyl-ether fraction derived from Thespesia garckeana for treating diabetes. In addition to augmenting the functions of antioxidant enzymes, the extract also impeded inflammatory reactions, thus showcasing antidiabetic effects in experimental models.…”
Section: The Blood Glucose Level In Rats Fed Azanza Garckeana Fruit P...supporting
confidence: 92%
“…For example, in a study conducted in Zimbabwe on fruits, the methanolic extract of the Uapaca Kirkiana fruits showed DPPH antioxidant activity in the range of 34:96% ± 0:86 to 36:68 ± 0:46% that was higher than the same species found in Malawi evaluated in this study (15.57%) [38]. Similar findings of antioxidant activity parameters for the studied plants showed similar results for the rest of the plants, namely, Ziziphus mauritiana [39], Parinari curatellifolia [40], Cocos nucifera [41], Thespesia garckeana [42], Vitex doniana [43], Adansonia digitate [44],…”
Section: Total Phenolic Content (Tpc) and Total Flavonoidsupporting
confidence: 80%